Glaucoma Prevalence in Diabetes Mellitus Patients at the Eye Policlinic, Prof. Dr. H. Aloei Saboe Gorontalo - Maria Margaretha; Naning Suleman (Universitas Negeri Gorontalo, 2022)
Introduction: Glaucoma is a disease of damage to the optic nerve that causes narrowing of the visual field and loss of visual function. One of the systemic conditions that can trigger glaucoma is diabetes mellitus. This study aims to determine the prevalence of glaucoma in diabetic patients at the Eye Polyclinic of RSUD Prof. Dr H. Aloei Saboe Gorontalo.Methods: This research used a descriptive retrospective study design on medical records at Eye Polyclinic of RSUD Prof. Dr H. Aloei Saboe Gorontalo from January to December 2020.Results: The results showed that from 12 cases of glaucoma in diabetes mellitus patients, there were more males, namely 8 patients (66.7%) and 4 patients (33.3%). Based on the age group, the most in the 40-60 year age group were 10 patients (84%). Based on the type of diabetes, all cases were found in type II diabetes, namely 12 patients (100%). Based on the length of time the patient had diabetes, it was found that 11 patients (92%) had diabetes 5 years.Conclusion: In patients with diabetes mellitus, the prevalence of glaucoma was more in men who had diabetes for a long time.